RED CELL ALLOIMMUNIZATION IN MULTITRANSFUSED THALASSAEMIA MAJOR PATIENTS - Moeen, Shazia; Farooq, Nazish; Irshad, Romana; Ashfaq, Muhammad; Farooq, Umer; Idris, Muhammad (Journal of Ayub Medical College Abbottabad, 2017)
Background: Lifelong transfusions are life savers for thalassaemia patients but are associated with many complications. Alloimmunization is a major problem for blood banks. Antigens of foreign red blood cells induce the formation of antibodies in patients suffering from thalassaemia. The purpose of this study was to examine the frequency of red cell alloantibodies and to express the type of these antibodies in thalassaemia patients. Methods: Patients that have received multiple transfusions were included in this study. Those with the positive Coombs test (DAT) results were excluded from the study and remaining patients were screened for antibodies. A panel of known blood group antigens was used for the patients who had a positive antibody screening test because they had alloantibodies in their serum. First, three cell panel was applied. If the screen was positive then eleven cell panel was used to identify the specific antibody. Both the cell panels were applied at room-temperature, liss (low ionic strength saline) and coombs phase. Results: Three hundred & two patients were selected out of which 65.6% (n=198) were males and 34.4% (n=104) females. Patient's age ranged from 1.5 years to 26 years ±5.40 years. All of the patients were given regular red cell transfusion at 2-4 weeks interval. They were given non leukodepleted transfusions. It is not the practice in any thalassaemia Centre in Pakistan to give phenotypically matched blood for Kell, Kidd, Duffy or any other minor group antigens to patients on regular blood transfusion. Alloimmunization was positive in 12 (4.0%) of the 302 patients studied. Male were 66.67% (n=8) and female were 33.33% (n=4). Samples of these positive patients were further tested to determine specificity of alloantibodies. Anti Cw was most common, detected in 4 out of 12 (1.3%) patients. Anti K, k, S and Lua were detected in 2 out of 12 (0.7%) each. Conclusion: Thalassemia major patients on regular blood transfusions can develop red cell alloantibodies. Detailed pre-transfusion screening would add towards better management of these patients. Keywords: Transfusion; thalassaemia major; Alloantibodies; antigens